Integrasi Human Capital Management dan Spiritualitas Islam dalam Meningkatkan Profesionalisme Guru Madrasah - Ubaidillah, Ubaidillah; Hresnawanza, Muhammad Heru (At Tadbir: Islamic Education Management Journal, 2025)
This study aims to analyse the application of Human Capital Management (HCM) in enhancing the professionalism of teachers based on Islamic spirituality in madrasahs. The research approach uses a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. This study focuses on how HCM principles are applied in teacher management, including aspects of recruitment, competency development, performance appraisal, and the integration of Islamic spiritual values into the madrasah work culture. The results show that the application of HCM is still simple and administrative in nature. The teacher recruitment process emphasises moral aspects and Islamic commitment rather than professional competence, while teacher development programmes have not been implemented systematically and sustainably. Teacher performance assessments do not yet reflect strategic HCM principles, but the values of sincerity, responsibility, and religious awareness are key strengths in building work ethic, loyalty, and teacher professionalism. The integration of Islamic spirituality has been proven to strengthen teachers' character and create a work culture based on religious values. This study contributes to expanding the concept of Islamic Human Capital Management by adding the dimension of spiritual capital as an important foundation in human resource development in Islamic educational institutions.